Gambaran Lama Terdiagnosa dan Kadar Glukosa Darah Sewaktu terhadap Nefropati Diabetik pada Penderita Diabetes Mellitus - Maulidan Nurun Nabila; Ahmad Ikhlasul Amal; Dwi Retno Sulistyaningsih (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Diabetic nephropathy remains a major microvascular complication contributing to morbidity among patients with diabetes mellitus, particularly in relation to prolonged disease duration and poor glycemic control. This study aimed to describe the distribution of diabetes duration and random blood glucose levels among patients with diabetic nephropathy. A retrospective descriptive design was applied using medical record data of diabetic nephropathy patients treated at Sultan Agung Islamic Hospital, Semarang, in 2025. A total of 97 patients were selected using the Taro Yamane formula. Data on duration of diabetes diagnosis and random blood glucose levels were analyzed using univariate analysis and presented as frequency and percentage distributions. The findings indicate that most patients with diabetic nephropathy had been diagnosed with diabetes for more than one year and exhibited elevated random blood glucose levels, reflecting sustained metabolic stress. These patterns support the concept that cumulative exposure to hyperglycemia over time plays a critical role in the development of renal microvascular damage. The study highlights the clinical relevance of early glycemic monitoring and long-term disease management to mitigate the progression of diabetic nephropathy.